Backstepping decentralized fault tolerant control for reconfigurable modular robots - Jinbao He; Xinhua Yi; Zaifei Luo; Guojun Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
For the actuators fault of reconfigurable modular robots, a backstepping decentralized fault tolerant control(DFTC) algorithm is proposed. The reconfigurable robot system is diviedinto a set of interconnected subsystems. The fault tolerant controller is designed based on backstepping method.DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2583